Curcumin: a review - Chauhan, Monika; Saha, Suman; Roy, Amit (Journal of Applied Pharmaceutical Research, 2014)
The main objective of this review article is to overcome or to improve the problems related with curcumin with the help of new technologies or modifications to make a promising therapeutic agent which gives a good therapeutic response. Curcumin, a known natural polyphenolic compound obtained from dietary spice turmeric, possesses pharmacologic effects including anti-inflammatory, antioxidant, and many other activities. Clinical trials on curcumin have shown its safety and efficacy even at high doses in humans. But inspite of that it shows poor bioavailability (oral bioavailability) which is one of the major problems regarding curcumin. There are other reasons contributing to the low plasma and tissue levels of curcumin appear to be due to poor absorption, rapid metabolism, and rapid systemic elimination. To improve the bioavailability of curcumin, numbers of approaches have been undertaken. These approaches involve, first, the use of adjuvant like piperine that interferes with glucuronidation; second, the use of liposomal curcumin; third, curcumin nanoparticles; fourth, the use of curcumin phospholipids complex; and fifth, the use of structural analogues of curcumin.